Cybersecurity in supply chain management (cybersecurity technology) - Siau, Timothy Chen Fu (Nanyang Technological University, 2022)
Supply Chain companies face increasing cyber threats as they look to improve their efficiency and processes. Cybersecurity is one of the most critical factors that businesses need to consider when it comes to improving their supply chain management. Most companies rely on software and data to track their goods' movement, making them vulnerable to cyber-attacks. Despite the technological advancements in cybersecurity, the increasing number of supply chain attacks has highlighted the need for more effective strategies to safeguard organisations' supply chains. While there has been a wide variety of studies on the subject, there are few studies to analyse the various aspects of cybersecurity in Singapore comprehensively. This paper aims to provide a comprehensive analysis of the current state of cybersecurity and its potential to improve the efficiency and processes of supply-chain companies. We have found that many Singapore companies need the security framework certification to operate as a secure supply chain organisation. This is a concern that the government has taken up to encourage companies to adopt effective digital strategies and improve their efficiency. Our surveys showed how many companies use various cybersecurity technologies to safeguard themselves. Additionally, we found that most IT professionals agree that the rise of digitalisation is the main reason the number of attacks has increased. To ensure that their operations are protected from cyberattacks, supply-chain companies in Singapore should work with the government to develop effective strategies and implement regulations.